A GWAS-supported variant interacting with diabetes predicts risk of atherothrombotic stroke in Han Chinese population. (1st February 2019) - Li, Zibao; Sun, Bo; Gu, Mengmeng; Wang, Mengmeng; Cheng, Xi; Lv, Jia; Cen, Si; Zhang, Shuai; Dai, Zhengze; Bai, Yongjie; Li, Shun; Wang, Guiling; et al.
Abstract: Background: A recent genome-wide association study has identified that rs4376531 variant conferred risk of atherothrombotic stroke (AS) in a Japanese population. This study was to explore the association in Han Chinese population. Methods: A total of 1036 cases and 643 healthy controls were enrolled. We genotyped rs4376531 variant with SNPscan. Multivariate logistic regression analysis was used to determine the association of genetic variation with risk of AS. Interaction analysis was examined by SNPStats web tool. Results: After adjusting for gender, age, body mass index (BMI), hypertension, diabetes and smoking, compared with CC genotype, we observed that GC and GG/GC genotypes were associated with a significantly decreased risk of AS (OR = 0.76, 95% CI = 0.58–0.99 and OR = 0.76, 95% CI = 0.58–0.98, respectively). The decreased risk was more obvious among subgroups with high BMI (OR = 0.63, 95% CI = 0.45–0.88), no hypertension (OR = 0.66, 95% CI = 0.46–0.94), diabetes (OR = 0.33, 95% CI = 0.17–0.64), and smoking (OR = 0.65, 95% CI = 0.44–0.95) in the dominant model (GG/GC vs CC). Interaction analysis also revealed that compared with non-diabetic patients with CC genotype, diabetic patients with CC genotype had a 4.48-fold (OR = 4.48; 95% CI = 2.98–6.72) increased risk of AS. Conclusion: Our data suggested that GC and GG/GC of rs4376531 contributed to a decreased risk of AS while CC genotype, interacting with diabetes, increased the stroke risk in Han Chinese population.